Environmental qualities and patient well-being in hospital settings - Frandsen, Anne Kathrine (Tidsskrift for Forskning i Sygdom og Samfund, 2013)
Within the last decades the impacts of the physical environments of hospitals on healing and health-care outcomes have been subject to ample research. The amount of documentation linking the design of physical environments to patient and staff outcomes is increasing. A Danish research project undertaken by Architecture and Design and the Danish Building Research Institute (Aalborg University) set out in 2008 to review research on the impact of the environmental qualities of health-care facilities on patients and staff. The objective of the review team was to develop a tool that would allow an overview of this research, needed by construction clients and decision-makers in Denmark responsible for large investments in future hospitals and healthcare environments in the decade to come. The present paper offers an overview of the findings of the review team. Its point of departure is the categorisation developed during the study, which facilitated the sorting and communication of the findings. In this categorisation, research findings are grouped according to their focus on specific spatial qualities – such as light and acoustics – and not according to the different diagnoses, which may be linked to such spatial qualities, like stress and depression. In other words, the application of this categorisation foregrounds the importance and the convenience of looking at spatial qualities of the physical environment, when addressing issues related to patient or staff wellbeing.